THE ROLE OF PHARMACISTS IN PHARMACEUTICAL SERVICES: A LITERATURE REVIEW - Fidi Setyawan; Ahmad Subagiyo; Milda Rianty Lakoan (Adisam Publisher, 2024)
Pharmaceutical services are an important component in the health care system. The role of pharmacists in pharmaceutical services has evolved along with changes in public health needs and developments in science. In order for treatment to be successful, pharmacists advise patients to adopt a healthy lifestyle. They also work with other health professionals to monitor the outcomes of treatment therapy that patients have completed. Pharmacists also consult, educate, and inform patients about the treatment therapy that they are undergoing. This emphasizes that pharmacists should increase their role in interacting with patients, be more oriented towards improving the quality of life of patients, so that the pharmacist's work orientation, which was previously only oriented towards medicine and tended to be behind the scenes, becomes a profession that is responsible for patients. Apart from that, pharmacists also play an important role in supporting the implementation of national health insurance and providing good pharmaceutical services. In managing a pharmacy, pharmacists are required to have knowledge and skills not only in the field of pharmacy, but also in the field of management. This is necessary so that the pharmacy can be managed properly and correctly.